Associated computational plasticity schemes for nonassociated frictional materials - Krabbenhoft, K.; Karim, M.R.; Lyamin, A.V.; Sloan, S.W. (2012)
A new methodology for computational plasticity of nonassociated frictional materials is presented. The new approach is inspired by the micromechanical origins of friction and results in a set of governing equations similar to those of standard associated plasticity. As such, procedures previously developed for associated plasticity are applicable with minor modification. This is illustrated by adaptation of the standard implicit scheme. Moreover, the governing equations can be cast in terms of a variational principle, which after discretization is solved by means of a newly developed second-order cone programming algorithm. The effects of nonassociativity are discussed with reference to localization of deformations and illustrated by means of a comprehensive set of examples.